Acute kidney injury after out of hospital pediatric cardiac arrest. (October 2018) - Cornell, Timothy T.; Selewski, David T.; Alten, Jeffrey A.; Askenazi, David; Fitzgerald, Julie C.; Topjian, Alexis; Holubkov, Richard; Page, Kent; Slomine, Beth S.; Christensen, James R.; Dean, J. Michael; Moler, Frank W.
Abstract: Importance: Many children with return of spontaneous circulation (ROSC) following cardiac arrest (CA) experience acute kidney injury (AKI). The impact of therapeutic hypothermia on the epidemiology of post-CA AKI in children has not been fully investigated. Objective: The study aims were to: 1) describe the prevalence of severe AKI in comatose children following out-of-hospital CA (OHCA), 2) identify risk factors for severe AKI, 3) evaluate the impact of therapeutic hypothermia on the prevalence of severe AKI, and 4) evaluate the association of severe AKI with survival and functional outcomes. Design: A post hoc secondary analysis of data from the Therapeutic Hypothermia after Pediatric Cardiac Arrest Out-of-Hospital (THAPCA-OH) trial. Setting: Thirty-six pediatric intensive care units in the United States and Canada. Participants: Of 282 eligible subjects with an initial creatinine obtained within 24 h of randomization, 148 were randomized to therapeutic hypothermia and 134 were randomized to therapeutic normothermia. Main Outcomes and measures: Primary outcome was prevalence of severe AKI, as defined by stage 2 and 3 Kidney Disease Improving Global Outcomes (KDIGO) consensus definition; secondary outcome was survival with a favorable neurobehavioral outcome. For this study, risk factors and outcomes were compared between those with/without severe AKI. Results: Of the 282 subjects enrolled, 180 (64%) developed AKI of which 117 (41% of all enrolled) developed severe AKI. Multivariable modeling found younger age, longer duration of chest compressions, higher lactate level at time of temperature intervention and higher number of vasoactive agents through day 1 of intervention associated with severe AKI. There was no difference in severe AKI between therapeutic hypothermia (39.9%) and therapeutic normothermia (43.3%) groups (p = 0.629). Survival was lower in those with severe AKI at 28 days (21% vs no severe AKI 49%, p < 0.001) and 12 months (21% vs no severe AKI 42%, p < 0.001). One year survival with favorable functional outcome was lower in those with severe AKI. Conclusions and relevance: Severe AKI occurs frequently in children with ROSC after OHCA, especially in younger children and those with higher initial lactates and hemodynamic support. Severe AKI was associated with worse survival and functional outcome. Therapeutic hypothermia did not reduce the incidence of severe AKI.